A ideologia da encenação: uma análise dos aspectos cênico/ideológicos da encenação produzida pela indústria cultural - Oliveira, Luciana Indaia Perdonsini de (2013)
The research that led to this dissertation adopted a set of scenic/ideological aspects inherent to the productions of the Culture Industry as its object of research. The intellectual output of Theodor W. Adorno and Max Horkheimer underscored the approaches on this subject, since it provides the same set of scenic/ideological features to be explored because, according to the authors, scenes produced by the culture industry are linked to the dominant ideology, since they act in favor of maintaining the status quo. The first objective was the definition this set of features inherent to the scene produced by the culture industry, through the exploration of literature produced by Adorno and Horkheimer, so it was possible to define a set composed of nine elements: Construction of characters as characteristic types; Stereotypes; Naturalization of Stereotyped language; Simplistic playwriting; Reuse dramatic formula; Love and sexuality as themes of plots; Utilization of tragic element; Objetive representation; Approximation of fiction and reality. The second goal was the analysis of scene produced by the culture industry nowadays, so that it was possible to verify if any scenic/ideological aspects indicated by Adorno and Horkheimer in the mid-twentieth century were present among the productions from this beginning of the twenty-first century. Through the analysis of three soap operas produced in Brazil in 2012, it was found that the nine scenic/ideological aspects as indicated by Adorno and Horkheimer appeared in the observed productions. Additionally, a new scenic/ideological feature, not indicated by Adorno and Horkheimer is present: the merchandising